Health behaviours during pregnancy in women with very severe obesity - Mohd Shukri, Nor Azwani; Duncan, A.; Denison, Fiona C.; Forbes, S.; Walker, Brian R.; Norman, Jane E.; Reynolds, Rebecca M. (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
The health behaviours of pregnant women with very severe obesity are not known, though these women are at high risk of pregnancy complications. We carried out a prospective case-control study including 148 very severely obese (BMI >40 kg/m2 ) and 93 lean (BMI < 0.05). Women with very severe obesity have low self-reported intakes and circulating levels of essential micronutrients in pregnancy and few follow current recommendations for pregnancy nutrition and lifestyle. These high-risk women represent a group to target for education about health behaviours prior to and during pregnancy.